Genital herpes and pregnancy - Tilli, Miguel (2023)
The genital infection due to herpes simplex virus (HSV) during pregnancy is uncommon, but in some cases may be dangerous to the newborn.The maternal-fetal transmission may occur during the primary infection at the onset of labor or due to reactivated latent maternal infection. The pre-sent revision focus on epidemiological, clinic, diagnosis and therapeutics aspects of HSV infection in pregnant women. Another aim is to offer pre-vention measures in order to reduce the risk of the perinatal transmission of the virus.